Magnetotelluric measurements along a reflection seismic profile: reprocessing and reinterpretation of MT data for crustal-scale electric resistivity structure in central Victoria, Australia - Lee, Seong Kon; Lee, Tae Jong; Uchida, Toshihiro; Park, In Hwa; Rawling, Tim; Cull, Jim; Song, Yoonho (Geosciences journal (Seoul, Korea), 2013)
Magnetotelluric(MT) soundings were done in Central Victoria, Australia, to investigate the electrical conductivity structure of the Bendigo and Melbourne structural zones. We reprocess and reinterpret the MT data, which were acquired along the same path as the seismic transect in 2006 by GeoScience Victoria (GSV). Deep crustal faulting in this region is considered to be responsible for significant mineralization and magmatic processes. The resulting two dimensional (2D) MT conductivity model is consistent with the seismic interpretation in that it clearly shows known boundaries as well, as additionally reveals four clearly isolated resistors, which could be hardly imaged by reflection seismic. With the result previously published, these resistors can be interpreted as granite or granodiorite intruded in the Devonian, or alteration associated with fluid migration. The 2-D electric conductivity model also agrees with seismic interpretations, which shows that internal faults in the Bendigo Zone are thrust fault systems with listric geometries that are connected in the mid-crust, and clarifies that the Bendigo Zone and Melbourne Zone experienced different tectonic evolution during the Benambran Orogeny in the Silurian. The model also supports the conjecture that the Melbourne Zone formed as a foreland basin to the uplifted Bendigo Zone.